Corporate Social Responsibility Yogyakarta International Airport dalam Perencanaan Pembangunan Kalurahan - Agus Pandu Purnama, R.Widodo Triputro (Program Studi Pembangunan Masyarakat Desa (D3), 2022)
Corporate Social Responsibility (CSR) Yogyakarta International Airport implements its program in supporting village development planning around the airport area. How the implementation of CSR activities with programs in village development planning is interesting to study. This research uses a qualitative descriptive method and an interactive approach, with data analysis techniques consisting of data reduction, data presentation and conclusion drawing/verification. The results of the study show that the Yogyakarta International Airport (YIA) CSR program has carried out its activities since the beginning of construction until now. The goal is to provide benefits for economic, social and environmental development, especially for the community around the airport working area. The Palihan Village is one of the villages in the airport working area which often receives CSR assistance. However, the implementation of the CSR program has not been integrated with village development and village development planning, so that it is less supportive of sustainable village development.